Food Green Cities: A Pathway to Sustainable Urban Development of Nepal - Shrestha, Sunil Babu (Nepal Journal of Science and Technology, 2021)
Urbanization is undergoing rapidly in Nepal. The causes are rural to urban migration and addition of municipalities by merging a number of rural areas. During the restructuring of the state, Government of Nepal declared 293 as municipalities among 753 local government units. Considering the municipalities as urban areas, urban population has reached more than sixty percent of Nepal’s total population. But the urban areas still have rural characteristics and insufficient infrastructures. Due to the increasing urbanization, the maintenance of sufficient open spaces, greeneries and the preservation of agricultural lands has become important urban issues in Nepal. The loss of productive lands has resulted in decrease of food self-sufficiency and green spaces in the cities. To tackle this urban issue, the Fourteenth National Development Plan has emphasized the concept of Food Green City (FGC) by integrating urban agriculture into urban planning. This paper aims to elaborate the concept of FGC and explore necessary policy intervention to realize the concept of FGC in practice based on the study of Godawari Municipality of Nepal. Finally, this study recommends FGC as a pathway for sustainable urban development of Nepal by highlighting FGC contribution in achieving Sustainable Development Goals (SDGs).